Time to Stop Routinely Prescribing Opiates after Carpal Tunnel Release. Issue 3 (March 2022) - Lalonde, Donald H.; Lalonde, Janice F.; MacDermid, Joy C.; Chung, Kevin C.; Gan, Bing Siang; Mierisch, Cassandra; Van Demark, Robert E.; Luc, Mario
Abstract : Background: North American surgeons continue to routinely order narcotic medication for postoperative pain relief after carpal tunnel surgery. For some patients, this instigates persistent use. This double-blind, multicenter trial investigated whether over-the-counter medications were inferior to opioid pain control after carpal tunnel release. Methods: Patients undergoing carpal tunnel release in five centers in Canada and the United States ( n = 347) were randomly assigned to postoperative pain control with (opioid) hydrocodone/acetaminophen 5/325 mg versus over-the-counter ibuprofen/acetaminophen 600/325 mg. The two primary outcome measures were the Numeric Pain Rating Scale (0 to 10) and the six-item Patient-Reported Outcome Measurement Information System Pain Interference T-score. Secondary outcome measures were total medication used and overall satisfaction with pain medication management. Results: The authors found no significant differences between opioid and over-the-counter patients in the Numeric Pain Rating Scale scores, Pain Interference T-scores, number of doses of medication, or patient satisfaction. The highest Numeric Pain Rating Scale group difference was the night of surgery, when opiate patients had 0.9/10 more pain than over-the-counter patients. The highest group difference in Pain Interference T-scores (2.1) was on the day of surgery, when the opiate patients had more pain interference than the over-the-counter group. Patient nationality or sex did not generate significant pain score differences. Conclusions: Pain management is not inferior for patients managed with over-the-counter acetaminophen/ibuprofen versus opioids. This study provides high-quality evidence that U.S. and Canadian surgeons should stop the routine prescription of narcotics after carpal tunnel surgery for patients who are not taking pain medicines daily before surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.